The Role of Critical Thinking in Helping Students Cope with Problems - Makhzoum, Violla; Komayha , Lama; Jabbour , Mazen (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: This research study aims to address the role of higher education programs in developing students’ critical thinking and problem-solving skills, emphasizing on the importance of the university professors’ role in nurturing these skills through the means they use in the classroom. The research also aims to highlight the difference in developing these skills among students between universities that follow the Francophone system and universities that follow the American system. Approach/Methodology/Design: To achieve the goal of this research, a descriptive approach was adopted to test the validity of the research hypotheses which are based on correlations between research variables related to higher education programs and the skill of critical thinking. A questionnaire was employed to collect data from the sample, which consisted of four private universities, divided into two groups which are two private universities that follow the American system, and two private universities that follow the Francophone system. The sample consisted of 120 students from universities that follow the American system, and 132 students from universities that follow the Francophone system. The students were selected from the Faculty of Economics and Business Administration. Findings: It was found out that there are statistically significant differences between the students’ answers regarding the extent of their ability to possess the skills of critical thinking and problem-solving in concerning to the universities in which they study, and we have also found that there are statistically significant differences in the student’s acquisition of these skills between the programs of Francophone and American universities according to their demographic characteristics and majors. Practical Implications: The study will be of great use for concerned authorities, emphasizing on critical thinking and problem-solving skills. Originality/value: The findings revealed a significant correlation between university programs and critical thinking and problem solving skills.